American Society of Maxillofacial Surgeons: The Last 25 Years and the Next 25 Years. Issue 2 (June 2022) - Yu, Jack C.; Lin, Alexander Y.
Professional organizations, like most complex human entities in the world including companies and countries, undergo periodic changes. Sometimes, these changes happen in years, while others may take decades or more. This year is the 75th anniversary of the American Society of Maxillofacial Surgeons (ASMS), a society born of necessity after World War II, even though its inception goes further back several decades. This brief article commemorates this important landmark and summarizes some key events of the last 25 years from 1997 to 2022, as others have nicely summarized the earlier periods. In addition to changes in clinical, research, and education in the context of craniofacial surgery, the review also examines from the national and global perspectives within which exists ASMS. These historical comparisons allow for appreciation of changes and, more importantly, permits the educated forecast of the future. It is our hope that from the lessons learned from the past will emerge a brighter, better tomorrow.